Etične dileme socialnih delavcev v rehabilitacijskih programih na URI-Soča - Korošec, Tanja (Rehabilitacija (Ljubljana), 2017)
Social workers are often confronted with ethical decisions. One of the fundamental competencies of our profession is the ability to recognise the ethical dimensions of complex situations in social work practice, and the ability to reflect upon and articulate ethical dilemmas. A look through the case examples shows that ethical dilemmas arise because of disagreement between normative systems: the societal, the legislative, the professional and the personal.
Keywords: ethical issues; ethics; etične dileme; normative systems; normativni sistemi; rehabilitacija; Rehabilitation; Social Work; socialno delo; vocational rehabilitation